2004
DOI: 10.1021/ef049940l
|View full text |Cite
|
Sign up to set email alerts
|

Axial Concentration Profiles and NO Flue Gas in a Pilot-Scale Bubbling Fluidized Bed Coal Combustor

Abstract: Atmospheric bubbling fluidized bed coal combustion of a bituminous coal and anthracite with particle diameters in the range 500-4000 µm was investigated in a pilot-plant facility. The experiments were conducted at steady-state conditions using three excess air levels (10, 25, and 50%) and bed temperatures in the 750-900°C range. Combustion air was staged, with primary air accounting for 100, 80, and 60% of total combustion air. For both types of coal, high NO concentrations were found inside the bed. In genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 72 publications
1
18
0
Order By: Relevance
“…Moreover, the mass transfer resistance increases between the bubble phase and fuel particle surfaces [60], which leads to an oxygen-lean condition for the fuel combustion. The intensified reducing atmosphere will restrain the transformation of char-nitrogen and volatile nitrogen of coarse fuel particle into NO x [9,61]. As shown in Fig.…”
Section: Formation and Reduction Of No X In Cfb Combustionmentioning
confidence: 99%
“…Moreover, the mass transfer resistance increases between the bubble phase and fuel particle surfaces [60], which leads to an oxygen-lean condition for the fuel combustion. The intensified reducing atmosphere will restrain the transformation of char-nitrogen and volatile nitrogen of coarse fuel particle into NO x [9,61]. As shown in Fig.…”
Section: Formation and Reduction Of No X In Cfb Combustionmentioning
confidence: 99%
“…The research results of Tarelho [17] and Li [18] indicated that, under the air-staged combustion condition, the decrease in α r normally led to the reduction of NO X emissions. However, when α r is too small, HCN, NH 3 and char-N in the reducing zone will increase quickly and will be oxidized in the burn out zone.…”
Section: Effect Of Combustion Parameters In the Reducing Zone On No Xmentioning
confidence: 99%
“…and is for that conducive to NO x destruction and therefore produce less NO x emissions until the furnace end [154,162,176]. The major problem regarding the residence time is that the temperature profiles inside a furnace cannot be calculated.…”
Section: Air Staging Influencementioning
confidence: 99%
“…which then are being oxidized into NO x in the downstream process when additional oxygen becomes available [176]. When the burner stoichiometric ratio is too high, oxygen is relative sufficient present in the primary combustion zone, and this weakens the reducing atmosphere and leads to form more …”
Section: Figure 15 Foster Wheeler Parallel Flow Split Flame (Vs / Sfmentioning
confidence: 99%
See 1 more Smart Citation